The Implementation of TPACK (Technological Pedagogical and Content Knowledge)-Based Learning: The Comparison of Students’ English Learning Outcomes Using the Blended Learning Model and Discovery Learning Model - Andi Bulkis Maghfirah Mannong; Sitti Maryam Hamid; Lilih Insyirah; Nur Hidayat (Journal of Development Research, 2021)
This study aims to determine the comparison of the English learning outcomes between the students who taught by Blended Learning model and Discovery Learning model. Moreover, this study also aims to reveal which model is more effective in enhancing the students’ English language learning outcomes. This experimental research involved two experimental classes in which the first experimental class taught using the Blended Learning model with the help of WhatsApp software (online class), while in the second experimental class taught using Discovery Learning model with the help of Power Point software (offline class). The sample who are involved in this study was 30 students. The data collected using writing test. The results showed that the students learning outcomes were increased in both the experimental 1 and 2. However, the mean score of the students who taught using Discovery learning is higher than the mean score of the students who taught using Blended Learning. Thus, it can be concluded that H1 was accepted and H0 was rejected. Further, the applying of Discovery Learning assisted by PowerPoint software is more effective than using Blended Learning model assisted by WhatsApp. The application of the Power Point-assisted Discovery Learning enables the students more focus as they take responsibility in learning, then it allows the students to learn pacely.